IMPACT OF COVID-19 ON FEMALE WORK PARTICIPATION IN INDONESIA: WHO IS MORE AFFECTED? - Pravitasari, Clalisca; Nahar, Faiza Husnayeni (Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This study aims to analyze the impact of Covid-19 on female work participation in Indonesia. Using microdata from the August 2020 National Labor Force Survey (Sakernas) conducted by the Central Statistics Agency, the study measures the impact through three indicators: unemployment, temporary non-working status, and reduced working hours. The survey included a sample size of 793,202 individuals aged 15 and over. Findings reveal that female workers are more likely to experience reduced working hours compared to male workers. These results highlight the disproportionate effects of the pandemic on women’s employment. The study underscores the need for targeted policy interventions to support women in the labor force, ensuring their economic resilience and recovery during and after the pandemic.